IMPLEMENTASI SELF ASSESSMENT SYSTEM (SAS) DALAM PEMUNGUTAN PROVISI SUMBER DAYA HUTAN (PSDH) DI KPH BONDOWOSO, KPH MOJOKERTO, DAN KPH MADIUN - Setiawan, Rahmat Budi; Suyunus, Mohamad (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2017)
Abstract: The Ministry of Environment and Forestry (KLHK) in 2016 transformed the timber forest product administration system into a self-assessment system (SAS) system. Specifically based on data on the realization of PSDH payments in 2015 (the period before SAS) and 2016 (period after SAS) in Perum Perhutani especially in KPH Bondowoso, KPH Madiun, and KPH Mojokerto indicate the existence of deviation of realization of PSDH revenue either increase or decrease from set target. The cause of deviations from the realization of PSDH revenues is known to be a problem in the preparation of PSDH targets that are not in accordance with the source data used in the formulation of targets and achievements of the sortimen realization that are not in accordance with the target. While the factors that encourage employees to meet the target RTT are known the rewards and punishment of the company. Strategies to improve the effectiveness of SAS implementation are done with the Mandor Tebang certification strategy, the timber numbering for all sortimen, and the socialization and support of related agencies. In order to improve employees loyalty can be implemented through a combination of preventing the emergence of intent by suppressing the source or opportunity to do so and the existence of audit actions and provide sanctions to someone who committed acts of forestry violations.